Comparison of Marginal and Internal Fit of CAD/CAM Ceramic Inlay Restorations Fabricated Through Model Scanner, Intraoral Scanner, and CBCT Scans - Ayben Şentürk; Bora Akat; Mert Ocak; Mehmet Ali Kılıçarslan; Kaan Orhan (Applied Sciences)
Background and Objectives: CBCT images have been successfully used for CAD/CAM crown restorations; however, their use for ceramic inlay restorations remains unclear. This study aimed to evaluate the marginal and internal fit of CAD/CAM ceramic inlay restorations fabricated using intraoral scanner, model scanner, and CBCT data. Materials and Methods: Inlay preparations were performed on 11 mandibular molar typodont teeth. The teeth were scanned using an intraoral scanner, an extraoral scanner, and CBCT (0.075 mm voxel size). CBCT-generated DICOM data were converted to STL format with dedicated software. All scan data were transferred to CAD software, and a total of 33 restorations were designed. Feldspathic ceramic blocks were used for milling. Micro-CT was employed to measure marginal and internal gaps, with 60 measurement points taken from three cross-sections per sample. Data were analyzed using ANOVA and Bonferroni tests (p < 0.05). Results: CBCT exhibited greater marginal and internal gap dimensions (mean: 169.27 ± 38.64 μm), which were approximately 60–70 μm higher than those of the intraoral (97.00 ± 10.1 μm) and model scanner groups (109.67 ± 9.72 μm), exceeding clinically acceptable limits (≤120 μm) (p < 0.05). Intraoral and model scanners showed similar, clinically acceptable results. Conclusions: CBCT was less accurate for inlay restorations, likely due to their complex geometry. Nevertheless, fabrication was possible, and further research may improve its clinical applicability.